The Construct of Identity in Hellenistic Judaism. Essays on Early Jewish Literature and History - Gruen, Erich S. (Deuterocanonical and Cognate Literature Studies, 2016)
This volume assembles twenty-three essays by Erich S. Gruen, who has written extensively on the literature and history of early Judaism and the experience of the Jews in the Greco-Roman world. Twenty-two of the articles have previously been published, and one new one was composed for the volume.